(untitled) (Applied Biological Research, 2017)
The study was conducted to compare ascorbic acid, β-carotene, chlorophyll and antioxidant activity of fresh and dry wheatgrass (Triticum aestivum L.)grown under indoor and outdoor cultivation. Three methods of drying i.e., shade-, oven- and freeze-drying were employed. All the three methods significantly reduced ascorbic acid, β-carotene, chlorophyll and antioxidant activity by 73.4 to 83.5, 38.7 to 73.4, 17.6 to 60.0 and 27.6 to 48.5%, respectively. Out of the three drying methods, oven-drying showed maximum reduction in all the parameters studied, followed by shade drying while least was observed in freeze drying method. Better retention of ascorbic acid and β carotene was in outdoor cultivation of wheatgrass; whereas, higher retention of chlorophyll and antioxidant activity was observed in indoor cultivated wheatgrass.